Strengthening opportunistic screening for hypertension: report from a tertiary care institution in a district of West Bengal, India - Ghosh, Ritu; Maulik, Sanghamitra; De, Saikat; Tikader, Tanmoy; Jha, Sankar Nath; Mondal, Sayantan; Mallik, Sarmila; Banerjee, Manju (International Journal Of Community Medicine And Public Health, 2019)
Background: Hypertension is a major public health problem in India and considered as a silent killer disease. The national program for prevention and control of cancer, diabetes, CVD and stroke (NPCDCS) recommended opportunistic screening for hypertension at all levels health facility. The present study was conducted with the objectives to estimate the magnitude of hypertension among the General OPD attendees aged 18 years and above in tertiary care hospital in a district of West Bengal and to find out the factors influencing hypertension among them. Methods: The study was a hospital based observational, descriptive study with cross sectional design and conducted among 244 study participants in 2018. Study variables included socio demographic factors and both modifiable and non-modifiable risk factors for hypertension. Results: In this study 40.2% subjects had normal blood pressure, 18.4% were known hypertensive and 101 (41.3%) people were newly diagnosed as having high blood pressure. Among known hypertensive, 75% had poor control of hypertension. Age, religion, family history of hypertension, body mass index (BMI) and central obesity had significant association with hypertension. Conclusions: The study recommended strengthening of opportunistic screening of all patients for hypertension at all levels of health care, especially through the village health nutrition day platform and providing treatment free of cost. Awareness generation and counselling for lifestyle modification should also be strengthened.